A Post-Pandemic, Nature-Based Tourism and Conservation : Recovery Plan for Rwanda - Benitez, Pablo; Blignaut, James; Kalisa, John; Katanisa, Peter; Rutebuka, Evariste; Mulisa, Alex (World Bank, Washington, DC, 2021)
The Rwandan economy has grown well above average compared to its peers and the world over for the past two decades achieving growth rates of more than 8% regularly with 2019 being 12.5 percent. While these growth rates have been achieved from a very low base, it has been the catalyst for a quadruple increase in the GDP/capita from $268 in 2000 to $837 in 2019. The prevailing Covid-19 pandemic, however, is undoing much of the hard-fought gains made in development over the past two decades. As a case in point, the GDP/capita declined to $816 in 2020, a decline in absolute terms of $21/capita, the largest decline since 1999. Additionally, thetourism sector saw a decline in the number of visitors to the National Parks of 67% to levels last seen in the early part of this millennium (RDB 2020). This decline coincides with loses in income and jobs. In additional there has been the complete collapse of the highly praised and well-functioning revenue sharing model whereby local communities benefitted from the proceeds the NationalParks were generating. The decline in park revenue also resulted in the conservation sector’s decreased ability to manage and maintain the National Parks. This has had a debilitating impact on the livelihoods of people living adjacent and near the conservation areas as well as all the people employed as well as enterprises within the tourism and conservation sector and value chain.